The safety and efficacy of bridging full-dose IV-IA thrombolysis in acute ischemic stroke patients with MCA occlusion: a comparison with IV thrombolysis alone - Sanak, Daniel; Kocher, Martin; Veverka, Tomas; Kral, Michal; Cerna, Marie; Zapletalova, Jana; Burval, Stanislav; Skoloudik, David; Bartkova, Andrea; Cechakova, Eva; Dornak, Tomas; Herzig, Roman; et al. (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
AIMS: Early recanalization of the occluded cerebral artery is substantial for clinical improvement in acute ischemic stroke (IS) patients. The rate of achieved recanalizations using IVT is low. The aim of this study was to compare the safety and efficacy of bridging full-dose intravenous-intraarterial (IV-IA) thrombolysis to IVT alone in acute IS patients with occluded MCA. METHODS: Seventy-nine consecutive IS patients with MCA occlusion were treated either with IVT alone (historic controls, Group 1) or with full-dose IV-IA thrombolysis (Group 2). Stroke severity was evaluated using NIHSS, achieved recanalizations using transcranial Doppler (Group 1) or angiography (Group 2). Occurrence of ICH including SICH was evaluated after 24 hours. 90-day clinical outcome was evaluated using modified Rankin Scale (mRS). RESULTS: Group 1 consisted of 50 patients (24 males, mean age 70.8±10.2 years) and Group 2 of 29 patients (14 males, mean age 67.8±10.0 years). No difference was found in the initial NIHSS (median 16 vs. 17) and other baseline parameters including time from stroke onset to IVT. Patients treated with bridging therapy had a higher number of achieved MCA recanalization (75.9 vs. 32.0%, P=0.0002), similar number of SICH (6.0 vs. 6.9%, P=1.000) and 34.5% of them achieved mRS 0-2 versus 28.0% of patients treated with IVT (P=0.546). Patients with shorter TR had significantly better clinical outcome (P=0.019). CONCLUSION: Bridging IV-IA thrombolysis seems to be safe and more effective than IVT alone in acute stroke patients with MCA occlusion.
Keywords: ischemie mozku; Brain Ischemia; Humans; Stroke; Thrombolytic Therapy; trombolytická terapie; Aged; Female; Ultrasonography; výsledek terapie; Middle Cerebral Artery; senioři; lidé; intraarteriální infuze; cévní mozková příhoda; ultrasonografie; ženské pohlaví; stupeň závažnosti nemoci; Male; arteria cerebri media; Treatment Outcome; Infusions, Intra-Arterial; Infusions, Intravenous; Severity of Illness Index; mužské pohlaví; intravenózní infuze